Outcomes of hemi- vs. total arch replacement in acute type A aortic dissection: A systematic review and meta-analysis - Ma, Likang; Chai, Tianci; Yang, Xiaojie; Zhuang, Xinghui; Wu, Qingsong; Chen, Liangwan; Qiu, Zhihuang (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Acute type A aortic dissections (AAAD) pose a challenge to surgeons due to high mortality, and decision making regarding the appropriate procedure is controversial. This study compared the outcomes of hemiarch and total arch replacement for AAAD. Methods: The PubMed, Web of Science, Embase and Cochrane databases were searched for comparative studies on hemiarch versus total arch replacement that were published before May 1, 2022. Results: We included 23 observational studies with a total of 4576 patients. Combined data analysis showed that early mortality (RR =0.82; 95% CI: 0.70-0.97; P=0.02), incidence of postoperative permanent neurological dysfunction (RR=0.72; 95%CI:0.54~0.94; P=0.02), and incidence of renal failure and dialysis (RR=0.82; 95%CI:0.71~0.96; P=0.01) were all lower for hemiarch than for total arch replacement. However, hemiarch replacement had a higher rate of late mortality (RR=1.37; 95%CI:1.10~1.71; P=0.005). There were no statistically significant differences between the two groups in terms of re-operation for bleeding, aortic re-operation, or postoperative pneumonia. Conclusions: In this study, hemiarch replacement had better early outcomes but a higher late mortality rate than total arch replacement. Decisions regarding the extent of arch repair should be made according to location and extent of AAAD and the experience of surgeons to ensure the most favorable prognosis.